EPQ Model for Trended Demand with Rework and Random Preventive Machine Time. (23rd June 2013) - Shah, Nita H.; Patel, Dushyantkumar G.; Shah, Digeshkumar B.
Abstract : Economic production quantity (EPQ) inventory model for trended demand has been analyzed with rework facility and stochastic preventive machine time. Due to the complexity of the model, search method is proposed to determine the best optimal solution. A numerical example and sensitivity analysis are carried out to validate the proposed model. From the sensitivity analysis, it is observed that the rate of change of demand has significant impact on the optimal inventory cost. The model is very sensitive to the production and demand rate.